Performance Enhancement of Biobattery from Tropical Almond Paste Using Acetic Acid Addition - Graziani Rumbino; Lili Maniambo; Melfi Soll; Gemala Dirgantari; Octolia Togibasa (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2023)
Biobattery is an alternative energy device that uses organic waste without hazardous chemicals. It is further reported that tropical almond (Terminalia catappa L.) is rich in glucose content, making it a potential electrolyte for a biobattery device, although the power performance is not optimal. Therefore, this research aims to improve the performance of biobattery from tropical almond paste with the addition of acetic acid. Biobattery cells were constructed using the galvanic cell method, while the tropical almond paste as an electrolyte was stored in a box container with a volume of 600 cm³, then attached with copper and zinc metal plate as cathode and anode. Five typical devices of biobattery were made with various acid concentrations of 0%, 10%, 20%, 40%, and 80% which were added to the electrolyte. The results showed a significant enhancement of power performance, from 0.25 mW without any acid up to 1.62 mW with acid addition. The biobattery from tropical almond paste added with acetic acid of 20% had the best performance. Based on the results, the characterization of this device had an open cell voltage of 0.93, and the power curve showed a peak value of 1.62 mW at a current of 3.29 mA, with a stable current lasting up to 200 hr.